Students’ Perception towards Written Feedback of Thesis Writing Advisory at STKIP Sidoarjo - Sabat, Yuliyanto; Slamet, Joko (JET ADI BUANA, 2019)
This research is aimed to find out the most used type of written feedback and the students’ perceptions towards lecturers’ written feedback on thesis writing advisory at STKIP PGRI Sidoarjo. This study employed descriptive qualitative method. The subjects of this study were the 7th semester students at STKIP PGRI Sidoarjo who were working the thesis writing. The source of data was the students’ writings consisting lecturers’ written feedback (indirect and direct written feedback). The instruments applied were documentation, questionnaire, and interview. The researcher distributed the questionnaires to 20 students and conducted the interview to 5 students to clarify and strengthen the data by seeing the most degree of agreement chosen. The result showed that the most type of written feedback was indirect written feedback consisting 337 items (65.44%). Meanwhile, the direct written feedback was 178 items (34.56%). The students had positive perceptions towards the lecturer’s written feedback. They preferred to get written feedback as it had been clear, useful and helpful for the students. It also could be a motivation and a guidance in the thesis writing. The researcher addresses suggestions to: lecturers to keep using written feedback by giving clear explanations and information; students to evaluate their thesis writing; other researchers to advance the implementation of written feedback; and the institution to considerate providing a new regulation deals with the efficiency of thesis writing advisory